Effect of Dancing and Nutrition Education on Hemodynamic and Autonomic Status in Adults with Metabolic Syndrome: a Randomized Controlled Clinical Trial (2016)
RESUMEN: Background:Although the benefits of exercise and changes in lifestyle on components of the metabolic syndrome (MS) have been described, little is known about the effect of dancing and nutritional changes on the cardiovascular system. Objective: Evaluate the effect of an intervention based on dancing and nutrition education on hemodynamic and autonomic status in adults with MS. Methods: A randomized controlled clinical trial was conducted involving 59 adults with MS. The intervention lasted 12 weeks and consisted of an aerobic exercise program (dancing) at an intensity of 60-75% of heart rate reserve, 60minutes 3 times a week, and muscle strength training at an intensity of 50% of a maximum repetition, 30minutes twice a week. The nutrition education program consisted of 2-hour workshops each week. Assessment of impedance cardiography and function of nervous system with analysis of heart rate variability (HRV) were made before and after the intervention. Results: In the intervention group, a decrease in mean arterial pressure of -7.8mmHg (95% CI, -12.84 to -2.75; P=0.004) was found as well as in the systemic vascular resistance (SVR) index of -864.29 dyn·s·m2/cm5 (95% CI, -1506.31 to -222.26; P=0.010). Increase was observed in the cardiac output index of 0.48 L/min/m2 (95% CI, 0.14 to 0.83; P=0.007). In the spectral analysis of HRV a reduction in LF/HF ratio of -0.52 (95% CI, -1.02 to -0.02; P=0.040) was also found. Conclusions: An intervention with dancing and nutrition education lowers arterial blood pressure and SVR and has favorable effects on the sympathovagal balance in patients with MS.